"Cursed by Coal": Climate Change and the Battle over Mining Limits in the Czech Republic. Issue 2 (1st February 2022) - Shriver, Thomas E.; Adams, Alison E.; Longest, Landen
Abstract: Global reliance on fossil fuels presents a significant obstacle to climate change mitigation. While numerous countries have committed to phasing out their reliance on fossil fuels, many have not followed through on their promises. We consider the Czech Republic, which is attempting to expand coal mining despite the industry's history of environmental devastation. Drawing on the literatures regarding elite legitimation and fossil fuel industries' legitimation strategies, we analyze the coal industry's campaign to remove mining limits that were established after the country's democratic transition in 1991. Data come from interviews and document analysis. While extant research has established how elites can reinforce their legitimacy, our research provides insight into the specific mechanisms deployed to diffuse potential legitimacy crises. Specifically, we found that elites utilized four mechanisms: amplification, vilification, pacification, and fearmongering. We conclude by providing a roadmap for future research analyzing elite strategies to defend actions that exacerbate climate change.